Implementasi Program Kampus Mengajar dalam Meningkatkan Mutu Pendidikan di Makassar - Fathahillah; Muhammad Aditya Eka Putra; Nurul Mukhlisah Abdal (Sakura Digital Nusantara, 2025)
This study aims to examine whether the implementation of the Kampus Mengajar (Teaching Campus) Program aligns with the established policies, as well as to analyze the teaching and learning process within the program. The research was conducted from February to March 2025 using a quantitative research method. Data were collected through observation, questionnaires, interviews, and documentation. The subjects of this study were students from the Informatics and Computer Engineering Education Study Program who had participated in the Kampus Mengajar Program, selected using purposive sampling, totaling 85 respondents. The results showed that the implementation of the program by the students was in the moderate category, with a percentage of 29.4%. Likewise, the teaching process carried out by the students met the educational quality standards on the process aspect and was also categorized as moderate, with a percentage of 41.2%. Inferential analysis further revealed a positive influence of the Kampus Mengajar Program on education quality within the Process Standard aspect, with a correlation coefficient (R) of 0.630 and a coefficient of determination (R Square) of 0.397. This indicates that 39.7% of the variance in education quality was influenced by the implementation of the program, while the remaining 60.3% was affected by other factors not examined in this study.